2016
DOI: 10.1016/s2352-3018(16)30050-9
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric HIV testing beyond the context of prevention of mother-to-child transmission: a systematic review and meta-analysis

Abstract: CitationPaediatric HIV testing beyond the context of prevention of mother-to-child transmission: a systematic review and meta-analysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 26 publications
2
36
2
1
Order By: Relevance
“…HIV testing within PMTCT programmes could be improved by addressing logistical challenges such as shortages of dried blood spot sample test kits [34]. Additionally, HIV testing could be performed in paediatric in-patient and out-patient clinics to ensure access to ART of HIV-positive children who dropped out of PMTCT programmes [35]. …”
Section: Discussionmentioning
confidence: 99%
“…HIV testing within PMTCT programmes could be improved by addressing logistical challenges such as shortages of dried blood spot sample test kits [34]. Additionally, HIV testing could be performed in paediatric in-patient and out-patient clinics to ensure access to ART of HIV-positive children who dropped out of PMTCT programmes [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Of the 416 consenting adult index cases, 259 (66.6%) were on ART for more than one year, 258 (62.0%) were non-pregnant females and 299 (71.9%) had only primarylevel education. The median (IQR) age of the adults was 37 [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] years. The remaining 15 consenting were paediatric index cases.…”
Section: Index Cases and Uptake Of Hh-htcmentioning
confidence: 99%
“…However, routine facility-based testing efforts, including provider-initiated testing and counselling (PITC) and interventions that systematically track untested children of HIV-infected patients and provide referrals for testing, can increase paediatric HIV testing. These strategies remain an important method of identifying children and young persons living with HIV in areas where human resources are inadequate for home-based testing [10,19,32,[37][38][39][40].…”
Section: Despite Country and International Guidelines Thatmentioning
confidence: 99%
“…A recent multi-regional analysis has shown that many children in low-income countries start cART at severe immunosuppression levels (62% and 65% in girls and boys) compared to high income countries (21% and 28% in girls and boys) [12]. Reasons for the late start are manifold and several studies evaluated acceptance of HIV testing, linkage to care and cART initiation [13]. However, few reported long-term outcomes [14] and none provided cancer data.…”
Section: Epidemiology Of Cancer In Hiv-infected Childrenmentioning
confidence: 99%